2023
DOI: 10.1002/ijop.12915
|View full text |Cite
|
Sign up to set email alerts
|

The personal growth resources of the adult population following the first months of the war in Ukraine

Abstract: We aimed to determine the peculiarities of personal growth resources among the adult population following the first months of the war in Ukraine. The study, which included 1257 respondents (32.3% male and 67.7% female, aged 18–61+ years), used the Posttraumatic Growth Inventory—Expanded, the Brief Resilience Scale, the Professional Hardiness Questionnaire and the General Self‐Efficacy Scale. We found the following descending sequence of expression of the components of personal growth: appreciation of life, spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…In particular, such personality traits as extraversion, conscientiousness, openness to experience, and agreeableness. The work performed by Kokun (2023) has showed that the main personal resources for the personal growth of the civil population under war stress are self-efficacy and such components of professional hardiness as professional commitment, professional control and professional challenge acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, such personality traits as extraversion, conscientiousness, openness to experience, and agreeableness. The work performed by Kokun (2023) has showed that the main personal resources for the personal growth of the civil population under war stress are self-efficacy and such components of professional hardiness as professional commitment, professional control and professional challenge acceptance.…”
Section: Introductionmentioning
confidence: 99%